Scaffolding A Conceptual Support For Personalized Arabic Vocabulary Learning Using Augmented Reality (AR) Enhanced Flashcards - Nurkhamimi Zainuddin; Muhammad Sabri Sahrir; Rozhan M. Idrus; Mohammad Najib Jaffar (Pusat Teknologi Maklumat & Fakulti Pendidikan, 2024)
Non-Indexed Publication